THE IMPACT OF GOOD CORPORATE GOVERNANCE, PROFITABILITY, AND OPERATING EFFICIENCY ON FINANCIAL PERFORMANCE (CASE STUDY ON BANKS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2022-2023) - Al Fauziah , Della; Hariyanto, Wiwit (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background: This study investigates the interplay between Good Corporate Governance (GCG), profitability, and operational efficiency on the financial performance of banks listed on the Indonesian Stock Exchange (IDX) from 2022 to 2023. Specific Background: With increasing scrutiny on corporate governance and financial metrics in the banking sector, it is imperative to understand how these elements contribute to financial outcomes. Knowledge Gap: Despite existing literature on corporate governance and profitability, limited research addresses their collective impact on the financial performance of Indonesian banks, particularly concerning operational efficiency. Aims: This research aims to analyze the effects of GCG, represented by institutional ownership and board composition, alongside profitability (Return on Equity) and operational efficiency (BOPO ratio) on banks' financial performance (Return on Assets). Results: The findings reveal that institutional ownership and board composition do not significantly impact financial performance; however, profitability has a positive and significant effect, while operational efficiency negatively affects financial performance. Novelty: This study contributes uniquely by highlighting the critical role of profitability in enhancing financial performance, alongside the implications of operational efficiency management. Implications: The results provide essential insights for bank management to strategize for improved financial performance and suggest that regulators should emphasize implementing effective GCG frameworks. By shedding light on the factors influencing bank performance, this study aims to support policymakers in enhancing the stability and efficiency of Indonesia's banking sector.